2018
DOI: 10.21508/1027-4065-2018-63-5-98-102
|View full text |Cite
|
Sign up to set email alerts
|

Dental health of adolescents with arterial hypertension: rationale for approaches to prevention using calcium glycerophosphate and magnesium chloride

Abstract: Summary. Objective: to characterize the dental health of adolescents with arterial hypertension and to increase its level with a complex of therapeutic and prophylactic measures based on the results obtained. The study included 130 adolescents (65 – with arterial hypertension and 65 – control group) of 14.3 ± 2 years old. The level of systolic blood pressure in the main group was higher than that of the adolescents in the control group (126.6 ± 12.6 mm Hg vs 113.2 ± 7.4 mm Hg, p=0.00009), while the level of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…The result of our research showed clinical signs of periodontitis in 32.7% of the adolescents with hypertension. That is higher than the incidence of this disease given in population-based studies (7-24%) [16,17] and in the study of a selective group of normotensive adolescents (9.2%) [18]. In the studied cohort, the frequency of conventional factors of cardiovascular and cardiometabolic risk associated with hypertension was also higher, which is consistent with the results of previous studies [19].…”
Section: Discussionsupporting
confidence: 90%
“…The result of our research showed clinical signs of periodontitis in 32.7% of the adolescents with hypertension. That is higher than the incidence of this disease given in population-based studies (7-24%) [16,17] and in the study of a selective group of normotensive adolescents (9.2%) [18]. In the studied cohort, the frequency of conventional factors of cardiovascular and cardiometabolic risk associated with hypertension was also higher, which is consistent with the results of previous studies [19].…”
Section: Discussionsupporting
confidence: 90%